2018
DOI: 10.1038/s41396-017-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of metabolic heterogeneity and diverse growth responses in isogenic bacterial cells

Abstract: Microorganisms adapt to frequent environmental changes through population diversification. Previous studies demonstrated phenotypic diversity in a clonal population and its important effects on microbial ecology. However, the dynamic changes of phenotypic composition have rarely been characterized. Also, cellular variations and environmental factors responsible for phenotypic diversity remain poorly understood. Here, we studied phenotypic diversity driven by metabolic heterogeneity. We characterized metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 82 publications
(93 reference statements)
4
26
0
Order By: Relevance
“…Within each biological replicate, at least 4 technical replicates were performed, and their average was used for the plot. excellent indicator of dead E. coli cells (40)(41)(42)(43)(44). We additionally confirmed that PI is a good indicator for cell death by ampicillin; when we incubated cells with ampicillin and PI for 80 min and spread them on an LB agar plate containing no ampicillin, none of the PI stained (PI+) cells grew (see SI Appendix, Supplementary Method for detail).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Within each biological replicate, at least 4 technical replicates were performed, and their average was used for the plot. excellent indicator of dead E. coli cells (40)(41)(42)(43)(44). We additionally confirmed that PI is a good indicator for cell death by ampicillin; when we incubated cells with ampicillin and PI for 80 min and spread them on an LB agar plate containing no ampicillin, none of the PI stained (PI+) cells grew (see SI Appendix, Supplementary Method for detail).…”
Section: Resultssupporting
confidence: 67%
“…One issue of PI is the loss of nucleic acids upon lysis by ampicillin. PI stains nucleic acids, but lysis results in the loss of cytoplasmic contents, including nucleic acids (40)(41)(42)(43)(44). Hence, lysed cells are, although they are clearly dead, not stained by PI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, efpR mutants always produced two types of colonies arising from a single clone, the type S (‘smooth’, similar to the WT) and the type EV (‘ efpR variant’). Both cell types have distinct phenotypic marks, highlighting that the S/EV switch phenomenon directly affects virulence and also drastically modifies bacterial cell physiology, especially by generating a form of metabolic heterogeneity in the population (Rosenthal et al ., ; Şimşek and Kim, ). The efpR ‐dependent molecular mechanism leading to the emergence of EV type cells remains to be discovered.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the difference in cell-cycle phase distribution between the subpopulations supports the latter. The combination of factors such as life history 33,50 , cell cycle phase 35,37 , cell age 51,52 , metabolic activity 53,54 , heterogeneous microenvironment 55 and biological noise 43,56 results in a distribution of different metabolic states within the population 57,58 . The metabolic state of the cell can affect its antioxidant capacity, therefore resulting in variability in sensitivity to oxidative stress as observed here.…”
Section: The Bi-stable Chloroplast Redox Response Is Light Dependentmentioning
confidence: 99%